Crk-associated substrate (Cas) signaling protein functions with integrins to specify axon guidance during development. - Huang, Z.; Yazdani, U.; Thompson-Peer, K.L.; Kolodkin, A.L.; Terman, J.R. (Development, 2007)
Members of the Cas family of Src homology 3 (SH3)-domain-containing cytosolic signaling proteins are crucial regulators of actin cytoskeletal dynamics in non-neuronal cells; however, their neuronal functions are poorly understood. Here, we identify a Drosophila Cas (DCas), find that Cas proteins are highly expressed in neurons and show that DCas is required for correct axon guidance during development. Functional analyses reveal that Cas specifies axon guidance by regulating the degree of fasciculation among axons. These guidance defects are similar to those observed in integrin mutants, and genetic analysis shows that integrins function together with Cas to facilitate axonal defasciculation. These results strongly support Cas proteins working together with integrins in vivo to direct axon guidance events.